Echo Chambers and Symbolic Violence: A Study of Vertical Conflict in the Digital Disinformation Era - Hayati, Mala; Ali, Yusuf; Triadi, Irwan; Setyawibawa, Rachmat; Uksan, Arifuddin (International Journal of Education, Vocational and Social Science, 2025)
The development of social media in Indonesia has fundamentally changed the landscape of public communication, from a limited information space to a massive and emotional participatory arena. This study analyzes how the framing of the issue of the Revision of the Indonesian National Armed Forces Bill (RUU TNI) on social media, particularly the X (Twitter) platform, shapes public opinion and drives collective behavior in the real world. Using a descriptive qualitative approach through content analysis and framing analysis, this study explores the mechanisms of disinformation dissemination, the formation of echo chambers, and the influence of peripheral persuasion on public attitudes. The results show that emotional framing and misinformation dominate digital conversations, reinforcing social polarization and weakening public rationality. This phenomenon shows a close relationship between the construction of digital opinion and the escalation of conflict, as seen in demonstrations against the revision of the TNI's Internal Security Forces ( ) Law in various regions. In the context of national security, these dynamics illustrate non military threats stemming from digital disinformation and low critical literacy among the public. Therefore, an inclusive public communication strategy, strengthening digital literacy, and cross-sector collaboration are needed to build an early warning system for potential social conflicts based on digital media.